Aplikasi Pembelajaran Prakarya Siswa SMPN 5 Baubau Berbasis Android - Mukmin, Muhammad; Atina, La; Rohminiar, Rohminiar (Jurusan Teknik Mesin, Universitas Halu Oleo, 2023)
Craft Education learning that occurs at SMP Negeri 5 Baubau is a teacher who teaches Craft Education giving new material directly to students where there is not the slightest understanding of the material, especially with the monotonous nature of the material so that it makes students less enthusiastic about learning . Every teacher must be more creative and innovative in delivering learning material by utilizing technological developments, especially in the use of smartphones. In this research, the authors wanted to design and build an Android-based Craft Learning Application for SMPN 5 Baubau Students. The aim is to make it easy for the teacher in the process of delivering material to be discussed in the next lesson, as well as to make it easy for students to learn and understand the material to be discussed before the learning process takes place in the classroom. This research was conducted using the method of observation, interviews, and literature review. The expected result is that the Android-based Craft Learning Application for SMPN 5 Baubau Students has been successfully created and implemented for students at school.